Promoting Woman’s Empowerment for Social Resilience in Post-Conflict Area of Lampung - Uswatun Hasanah (Proceeding International Conference on Religion, Science and Education, 2023)
The rich diversity in Indonesia not only gives many good opportunities but also often triggers various social conflicts. In some areas, these social conflicts escalated into crimes and the brutal massacre of many innocent people, including in Lampung Province. Therefore, the effort to mediate and preserve peacefulness even after the conflict should be the main concern for all parties involved. In this case, women have a very crucial contribution, especially in the development of post-conflict social resilience. This study aims to examine the strategy of empowering women that could strengthen social resilience in Post-Conflict areas of Lampung Province. This research can be categorized as qualitative research, with interviews being the main instrument in this research data collection method. At the same time, observation is used to strengthen the interview data and a triangulation step for the validity of the research data. The research subjects taken were two sub-districts in Lampung Province which had the highest levels of social conflict, namely South Lampung and Central Lampung, which focused on female research subjects who had special social status and positions in the surrounding community. This study will reveal what aspects the woman’s empowerment can be optimized to sustain and improve the better situation after conflicts and how it will be better implemented for better future generations.